2012
DOI: 10.7860/jcdr/2012/4550.2538
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Serum Antibodies to TORCH Infection in and Around Varanasi, Northern India

Abstract: Background:The acute infections which are caused by Toxoplasma gondii, Rubella virus, Cytomegalovirus (CMV) and the Herpes Simplex Virus (HSV-2) during pregnancy are often associated with adverse foetal outcomes and reproductive failures. In the Indian context, the exact seroprevalence of these infections is not known due to unavailability of baseline data. Aims:The present study was undertaken to determine the serological evidence of the acute TORCH infections in women who were in the first trimesters of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 8 publications
5
32
2
4
Order By: Relevance
“…A comparison of seroprevalence in different population of antenatal cases is given in the Table 1. In our study Toxoplasma IgM positivity was similar to study done by Sen et al 5 But we there was marked difference with the study by Turbadkar et.al 6 where Toxoplasma IgG positivity was much higher 42.10% as compared our study 9.70%. But we had higher positivity for IgM 18.25% as compared to 10.5% in their study.…”
Section: Discussioncontrasting
confidence: 45%
“…A comparison of seroprevalence in different population of antenatal cases is given in the Table 1. In our study Toxoplasma IgM positivity was similar to study done by Sen et al 5 But we there was marked difference with the study by Turbadkar et.al 6 where Toxoplasma IgG positivity was much higher 42.10% as compared our study 9.70%. But we had higher positivity for IgM 18.25% as compared to 10.5% in their study.…”
Section: Discussioncontrasting
confidence: 45%
“…1 Total Seropositvity of high risk pregnant women in relation to type of bad obstetric outcome [35][36][37]. IgM seropositvity of 42.5 and 19.4 % was observed in studies from North Zone [38,39]. In the present study, the protective role (OR = 0.21) of toxoplasmosis towards HRP could be due to prior infection long time ago, and the immunity conferred might have prevented the parasite from crossing the placenta and in turn protected the fetus [40].…”
Section: Discussionmentioning
confidence: 99%
“…The present studies of Rubella antibodies were found IgG 69.09% and IgM (2.15%), in HIV negative women which is very high as compare to findings in Mumbai (26.00%) Turbadkar et al [2] and IgM antibodies in 30.4% in Varanashi Sen et al [21]. The risk of the congenital Rubella infection following a maternal infection ranged from 5% to 50% in various studies, with an increasing severity when it was acquired in the first trimester of the pregnancy Miller et al [31].…”
Section: Rubellamentioning
confidence: 55%
“…In present studies prevalence was found (3.47% for IgM and 20.66% for IgG) next to Mumbai. The prevalence for Toxoplasma was 20.93% IgG, 6.97% IgM at Hyderabad Sadik MS et al [19], Vellore 20.9% IgG, 11.9% IgM Ponutoti M et al [20], Varanashi 19.7% IgM Sen et al [21], Pune 19.44% IgG Natu et al [17], and Pune 18.25% IgM, 09.73% IgG Lavan Singh et al [22]. Highest rate of prevalence for Toxoplasma IgG was (94%) was reported in Iraq by Mossa HAL [23] and in Bahrain 15.8% was reported by Tabbara & Saleh [24].…”
Section: Torch Infection In Hiv Negative Womenmentioning
confidence: 99%